PERAMPASAN KEUNTUNGAN PERUSAHAAN SEBAGAI BENTUK PERTANGGUNGJAWABAN KORPORASI ATAS TINDAK PIDANA KORUPSI - Fadilah, Fatma Putri; Sentosa, Ummu Hani; Rasya, Harlin Sabrinda (Fakultas Hukum Universitas Pembangunan Nasional Veteran Jakarta, 2025)
(Corruption is an extraordinary crime that has a significant impact on state finances. One of the approaches applied in efforts to eradicate corruption is profit confiscation, which is a legal mechanism that authorizes the state to confiscate profits obtained illegally by a business entity. This research aims to analyze the effectiveness of the implementation of the mechanism of corporate profit confiscation in the recovery of state finances due to corruption in Indonesia. This research uses normative juridical method with statute approach and conceptual approach. Data is collected through literature study with primary and secondary legal sources. The results show that although profit forfeiture has been regulated in various laws and regulations, its implementation still faces obstacles, such as weak coordination between law enforcement agencies, unclear regulations, and lack of effectiveness in applying sanctions against corporations involved in corruption crimes. The implementation of profit forfeiture mechanisms in several countries, such as the United States and the United Kingdom, shows that this policy can be an effective instrument in recovering state assets and eradicating corporate corruption. Therefore, it is necessary to optimize regulations, increase the capacity of law enforcement officials, and strengthen inter-agency coordination so that the profit forfeiture mechanism can be applied more effectively in dealing with corruption cases in Indonesia).